Optimal CdS Buffer Thickness to Form High-Quality CdS/Cu(In,Ga)Se-2 Junctions in Solar Cells without Plasma Damage and Shunt Paths - Cho, Kyung Soo; Jang, Jiseong; Park, Jeung-Hun; Lee, Doh-Kwon; Song, Soomin; Kim, Kihwan; Eo, Young-Joo; Yun, Jae Ho; Gwak, Jihye; Chung, Choong-Heui (AMER CHEMICAL SOC, 2020)
CdS has been known to be one of the best junction partners for Cu(In,Ga)Se-2 (CIGS) in CIGS solar cells. However, the use of thick CdS buffer decreases the short-circuit current density of CIGS solar cells. There are two obstacles that limit the use of ultrathin CdS. The first is plasma damage to CIGS during the preparation of transparent conducting windows and the second is a low shunt resistance due to the direct contact between the window and CIGS via pinholes in the thin CdS buffer. In other words, to avoid plasma damage and shunt paths, we may have to use a CdS buffer that is thicker than necessary to form a high-quality CdS/CIGS junction. This work aims to determine how thin the CdS buffer can be employed without sacrificing device performance while also eliminating the above two obstacles. We investigate the effect of CdS thickness on the performance of CIGS solar cells with silver nanowire-based window layers, which can eliminate both obstacles. An approximately 13 nm thick CdS buffer allows us to achieve high short-circuit current density and fill factor values. To attain an even high open-circuit voltage, an additional CdS buffer with a thickness of 13 nm is needed. The data from this study imply that an approximately 26 nm thick CdS buffer is sufficient to form a high-quality CdS/CIGS junction.
Keywords: CU(IN,GA)SE-2 THIN-FILMS; EFFICIENCY; ELECTRODES